2009
DOI: 10.1002/adsc.200900239
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Aerobic Oxidation of Alcohols using a Hydrotalcite‐Supported Gold Nanoparticle Catalyst

Abstract: Hydrotalcite-supported gold nanoparticles (Au/HT) were found to be a highly efficient heterogeneous catalyst for the aerobic oxidation of alcohols under mild reaction conditions (40 8C, in air). This catalyst system does not require any additives and is applicable to a wide range of alcohols, including less reactive cyclohexanol derivatives. This Au/HT catalyst could also function in the oxidation of 1-phenylethanol under neat conditions; the turnover number (TON) and turnover frequency (TOF) reached 200,000 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
143
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 194 publications
(153 citation statements)
references
References 40 publications
8
143
1
1
Order By: Relevance
“…However, metal salts have been seldom used as supports for making gold catalysts [73,[133][134][135][136][137][138][139][140][141][142][143][144]. This is so, not only because the bulk of gold catalysis papers have been following the classic work of Haruta and co-workers who used metal oxide supports [15][16][17], but also because compared with metal salts, metal oxides are more frequently encountered in heterogeneous catalysis.…”
Section: Au/metal Phosphatesmentioning
confidence: 97%
“…However, metal salts have been seldom used as supports for making gold catalysts [73,[133][134][135][136][137][138][139][140][141][142][143][144]. This is so, not only because the bulk of gold catalysis papers have been following the classic work of Haruta and co-workers who used metal oxide supports [15][16][17], but also because compared with metal salts, metal oxides are more frequently encountered in heterogeneous catalysis.…”
Section: Au/metal Phosphatesmentioning
confidence: 97%
“…5). Although many nanogold catalysts [7] supported on hydrotalcite [30], titania [31], ceria [31], and gallia [32] catalyze this reaction with O 2 , only recently was bulk gold reported to catalyze this reaction and then only under more strenuous conditions (90°C, 5 atm O 2 ) [33].…”
Section: Au-catalyzed Decomposition Of Amine N-oxidesmentioning
confidence: 99%
“…Therefore, economical and environmental oxidants have been developed. To date, numerous transition-metalcatalyzed aerobic oxidations of alcohols have been developed, such as palladium [15,16], gold [17] and ruthenium [18]. Besides, Uyanik [19] found that the catalytic system consisting of HBr/NaNO 2 was effective for the aerobic oxidation of alcohols.…”
Section: Introductionmentioning
confidence: 98%